Автоматизація реєстрування вхідної кореспонденції на підприємстві з використанням офісного пакету - Білущак, Тетяна; Москалюк, Юлія (Видавництво Львівської політехніки, 2012)
The relevance of computer facilities while working with the office documents, which are an effective factor in improving staff productivity and quality in their work with documentation, is discussed in the article. In particular, the question of the feasibility of using electronic registration is revealed and the creation by designing a database for the incoming correspondence of the office using an Access software product, as a rational and efficient work with documents, is proposed.
Keywords: computer facilities; database; incoming correspondence registration